Climate Extreme Versus Carbon Extreme: Responses of Terrestrial Carbon Fluxes to Temperature and Precipitation. Issue 4 (8th April 2020) - Pan, Shufen; Yang, Jia; Tian, Hanqin; Shi, Hao; Chang, Jinfeng; Ciais, Philippe; Francois, Louis; Frieler, Katja; Fu, Bojie; Hickler, Thomas; Ito, Akihiko; Nishina, Kazuya; et al.
Abstract: Carbon fluxes at the land‐atmosphere interface are strongly influenced by weather and climate conditions. Yet what is usually known as "climate extremes" does not always translate into very high or low carbon fluxes or so‐called "carbon extremes." To reveal the patterns of how climate extremes influence terrestrial carbon fluxes, we analyzed the interannual variations in ecosystem carbon fluxes simulated by the Terrestrial Biosphere Models (TBMs) in the Inter‐Sectoral Impact Model Intercomparison Project. At the global level, TBMs simulated reduced ecosystem net primary productivity (NPP; 18.5 ± 9.3 g C m −2  yr −1 ), but enhanced heterotrophic respiration (Rh; 7 ± 4.6 g C m −2  yr −1 ) during extremely hot events. TBMs also simulated reduced NPP (60.9 ± 24.4 g C m −2  yr −1 ) and reduced Rh (16.5 ± 11.4 g C m −2  yr −1 ) during extreme dry events. Influences of precipitation extremes on terrestrial carbon uptake were larger in the arid/semiarid zones than other regions. During hot extremes, ecosystems in the low latitudes experienced a larger reduction in carbon uptake. However, a large fraction of carbon extremes did not occur in concert with either temperature or precipitation extremes. Rather these carbon extremes are likely to be caused by the interactive effects of the concurrent temperature and precipitation anomalies. The interactive effects showed considerable spatial variations with the largest effects on NPP in South America and Africa. Additionally, TBMs simulated a stronger sensitivity of ecosystem productivity to precipitation than satellite estimates. This study provides new insights into the complex ecosystem responses to climate extremes, especially the emergent properties of carbon dynamics resulting from compound climate extremes. Plain Language Summary: Terrestrial ecosystems sequestrate a large amount of carbon dioxide from the atmosphere, which helps to mitigate climate warming. Climate extremes, such as droughts and heatwaves, play a significant role in determining the capacity of land ecosystems in carbon uptake. In the past decades, terrestrial biosphere models have been widely used to investigate the magnitude and variations of carbon fluxes between land and the atmosphere. In this study, we attempted to understand how model‐simulated carbon fluxes respond to climate anomalies and extremes at the global level and across regions. Analysis of model simulations showed significant spatial variations in the sensitivity of carbon fluxes to climate variations. Interestingly, concurrences of abnormal temperature and precipitation could have stronger impacts on carbon fluxes than individual temperature or precipitation extreme event. This study is important for better understanding climate extreme impacts on ecosystem dynamics and the global carbon cycle. Key Points: Impacts of temperature or precipitation extremes on carbon fluxes could be amplified due to their interactive effects Hot extremes lead to a larger carbon loss in tropics while ecosystems in the arid and semi‐arid zones show the largest sensitivity to precipitation Models simulated larger sensitivity of ecosystem productivity to precipitation than satellite product, particularly in tropics